Study on the Water Quality Index (WQI) of Parit Besar River in Batu Pahat - Ahmad Salim, Nur Fadzillah; Kasmin, Hartini (Journal of Advancement in Environmental Solution and Resource Recovery, 2022)
Water resources play an important role in supplying water for domestic, industrial and agricultural. More than 70% of the Earth’s surface was covered with water sources were found in rivers, lakes, rainwater, groundwater, and others. However, over time, water quality deteriorates due to exposure to weather changes and urbanisation, and effects from point and non-point sources of pollution. The objectives of this study were to measure the Water Quality Index (WQI) parameters and identify the Parit Besar River latest status based on the WQI and National Water Quality Standards (NWQS) for Malaysia. Water samples were collected from three locations along the Parit Besar River and was analysed using six WQI parameters: the Ammonia Nitrogen (AN), Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Dissolved Oxygen (DO), pH, and Total Suspended Solids (TSS). In all upstream, middle and downstream sampling locations and WQI analyses, results show that the status of the Parit Besar river falls in Class IV. Meanwhile, the average NQWS Class of each parameter for AN, BOD, COD, DO, pH and TSS are 2.25 mg/L (Class IV), 6.18 mg/L (Class IV), 66.50 mg/L (Class IV), 6.15 mg/L (Class IIA), 6.86 (Class I) and 343.33 mg/L (Class V), respectively. It can be concluded that with the high population and high development of housing areas surrounding Parit Besar river have been leading this river to be highly contaminated, and this river is not appropriate for water supply or fisheries, hence it can only be used for irrigation purposes.